2019
DOI: 10.3389/fpubh.2019.00314
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Short-Term Health Coaching on Diabetes Control and Self-Management Efficacy: A Quasi-Experimental Trial

Abstract: Introduction: The aim of this study was to explore the effectiveness in HbA1c lowering and self-efficacy of diabetes self-management of a 6 months coaching intervention.Methods: This paper was a two-armed coaching intervention study in which 116 participants who presented type 2 diabetes were recruited at a medical center. The intervention group had health coaching and usual care for 6 months, whereas the control had usual care only. The main outcome variables were HbA1c level and self-efficacy of diabetes sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…Also, this finding is consistent with the recent Egyptian study that reported a significant decrease in HbA1c among type 2 diabetic patients who received a lifestyle education in the form of 48 weekly sessions over a 1-year period (HbA1c mean level 11.3 to 8.4, p < 0.001) [5]. Similarly, another study in Taiwan indicated that a 6-month health coaching by a professional coach reduced HbA1c in type 2 diabetic patients by 0.68% [11].…”
Section: Discussionsupporting
confidence: 90%
“…Also, this finding is consistent with the recent Egyptian study that reported a significant decrease in HbA1c among type 2 diabetic patients who received a lifestyle education in the form of 48 weekly sessions over a 1-year period (HbA1c mean level 11.3 to 8.4, p < 0.001) [5]. Similarly, another study in Taiwan indicated that a 6-month health coaching by a professional coach reduced HbA1c in type 2 diabetic patients by 0.68% [11].…”
Section: Discussionsupporting
confidence: 90%
“…A detailed description of our health coaching intervention has previously been published (15). The coaching was provided by a single coach who had over 120 h certified coach training and received the International Coach Federation's (ICF) Associated Certified Coach (ACC) credential and a master's degree in public health.…”
Section: Interventionmentioning
confidence: 99%
“…Although limited, research has supported the use of health coaching interventions for adults with prediabetes and type 2 diabetes to increase knowledge, increase motivation, and support long-term behavioral changes. For example, health coaching has been used to improve diet quality, exercise adherence, diabetes self-efficacy, diabetes empowerment, social support, and reduce diabetes distress in individuals with type 2 diabetes [10][11][12][13]. For adults with prediabetes, DeJesus et al [14] found that a 12-week wellness coaching program improved physical activity, healthy eating behaviors, self-efficacy, and quality of life.…”
Section: Introductionmentioning
confidence: 99%